UNDERSTANDING MARKET NARRATIVES: AN INTERDISCIPLINARY APPROACH TO IDENTIFICATION AND ANALYSIS - Hayrapetyan, Davit (Modern Psychology, 2025)
Market narratives - collectively shared stories and economic discourses - significantly influence investor behavior, market sentiment, and asset pricing dynamics. The concept of narrative economics, pioneered by Robert Shiller, underscores the importance of understanding the propagation and impact of these narratives, particularly in today's digital era, where social media and digital news rapidly disseminate market stories. Despite the acknowledged importance, systematic identification and analysis of market narratives pose significant methodological challenges. Narratives are inherently subjective, dynamically evolving, and often embedded within large volumes of noisy textual data. This complexity complicates efforts to pinpoint narrative emergence, measure their influence on financial markets, and differentiate meaningful signals from market noise.This article addresses the critical challenges associated with the scientific identification and analysis of market narratives. We explore interdisciplinary methodologies, integrating insights from behavioral finance, natural language processing (NLP), and machine learning to offer robust frameworks for narrative detection and assessment. The study critically reviews and evaluates methods including Structural Vector Autoregressions (SVARs) with narrative restrictions, redescription mining, storytelling algorithms, narrative mapping, news clustering, and textual analysis. Using empirical case studies, particularly focused on Microsoft Corporation, the effectiveness of each technique is analyzed, highlighting their respective strengths and limitations.Our research proposes a hybrid analytical framework that combines news clustering, narrative mapping, and advanced NLP techniques for improved narrative coherence, enhanced thematic clarity, and effective sentiment analysis. By advancing the science of market storytelling, this approach provides investors, analysts, and policymakers with actionable insights, enhancing their ability to anticipate market shifts, manage financial risks, and maintain market stability.
Keywords: Market narratives; Narrative economics; Behavioral finance; Investor sentiment; Natural language processing (NLP); Machine learning; Narrative identification; Sentiment analysis